Determination of systems with a steady equilibrium in vodkas, depending on transformation of hydroxyl protons - Kuzmin, Oleg (My University, 2015)
Eduction of steady equilibrium of hydroxyl proton of ethanol and water in various types of vodkas, which are produced in Ukraine.
Keywords: 1H ЯМР спектроскопія; 1H NMR spectroscopy; водно-спиртова суміш; водно-спиртовая смесь; aqueous-alcoholic mixture; кафедра технології ресторанної і аюрведичної продукції